1989
DOI: 10.1161/01.str.20.11.1524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of middle cerebral artery occlusion on cerebral cortex choline and acetylcholine in rats.

Abstract: We measured regional cerebral blood flow and acetylcholine and choline concentrations in tissue fragments of normally perfused and ischemic cortical regions from 10 rats. Tissue uptake of [ l4 C]iodoantipyrine was used to indicate regional cerebral blood flow, and gas chromatographymass spectrometry was used to measure acetylcholine and choline concentrations. Cerebral cortical ischemia was induced by permanent occlusion of the middle cerebral artery, and variables were measured 2.5 or 24 hours later. A close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…29 It was reported that the acetylcholinesterase-positive fiber density was significantly reduced in the cortex on the occluded side and the acetylcholine levels in the infarcted cortex were significantly decreased. 29 " 31 Based on the results cited above, the memory disturbance observed in this study is ascribed to the impairment of cerebral neocortex.…”
Section: Discussionsupporting
confidence: 62%
“…29 It was reported that the acetylcholinesterase-positive fiber density was significantly reduced in the cortex on the occluded side and the acetylcholine levels in the infarcted cortex were significantly decreased. 29 " 31 Based on the results cited above, the memory disturbance observed in this study is ascribed to the impairment of cerebral neocortex.…”
Section: Discussionsupporting
confidence: 62%
“…Enhanced choline production has been found to be limited to brain tissue fractions containing membranes. 46 A recent in vitro experiment found that choline levels were not decreased by treatment with an acetylcholinesterase inhibitor during ischemia, implying that phospholipid membrane breakdown and not acetylcholine metabolism was responsible for the rise in choline. 48 These studies suggest that increases in trimethylamine signal may arise from cell membrane breakdown.…”
Section: Ppmmentioning
confidence: 99%
“…5 The difference between that decrease and the presently reported larger decrease in tissue acetylcholine content is probably related to the fact that CBF levels attained during four-vessel occlusion are lower than those obtained with MCA occlusion. Although we did not measure CBF during ischemia in the present experiments, data in the literature indicate that blood flow in the rat cerebral cortex is <0.04 mlxg^xmin" 1 with four-vessel occlusion 9 while our previous experiments with MCA occlusion showed a minimum of 0.2 mlxg^xmin" 1 .…”
Section: Resultsmentioning
confidence: 61%
“…Acetylcholine, choline, and [ M C]IAP were extracted from these homogenates and assayed by gas chromatography/mass spectrometry (acetylcholine and choline) or liquid scintillation counting ([ 14 C]IAP) as described in detail elsewhere. 5 Regions dissected were the dngulate cortex, medial frontoparietal cortex, lateral frontoparietal cortex, olfactory cortex, rostral hypothalamus, medial striatum, lateral striatum, hippocampal CA1 region, and hippocampal CA2 region. All regions were sampled in both cerebral hemispheres.…”
Section: Methodsmentioning
confidence: 99%